High Throughput Virtual Screening For Inhibitors Of Salmonella typhi’s Dalanine- D-Alanine Ligase A - Tan, Chen Shen (2015)
Increasing numbers of multi-resistance Salmonella typhi cases poses a huge threat especially to ongoing typhoid treatments. This turn of event calls for new treatments against Salmonella typhi. The objectives of this study is to identify potential drug targeted protein from Salmonella typhi using high throughput virtual screening, and to understand the inhibition mechanism between ligand and protein. This research looks into the high throughput virtual screening of D-alanine-D-alanine ligase A against the ZINC database for potential inhibitors. D-alanine-D-alanine ligase A is a vital enzyme in the peptidoglycan biosynthesis pathway, and being a non-human homolog,